Students’ perception on using podcast to improve listening skills at 3rd semester english department of universitas bandar lampung - Prastyo, Yanuar Dwi; Dianingsih, Ajeng; Farhana, Siti ((JELE) Journal Of English Language and Education, 2023)
Listening skill is a process of catching what the speaker says, getting the speaker’s idea, and listening also consists of a speaker, listener, and sound. The objective of this research is to explore students’ perceptions of using podcasts to improve listening skills in the 3rd semester English Department of Universitas Bandar Lampung. This research was qualitative research. The research was done at the English Department of Universitas Bandar Lampung and consisted of 34 students. Data gathering was done by doing a questionnaire and interviews with 5 students. The data was analyzed by combining the results from the questionnaire and interview. The results indicated that there are improvements after using podcasts as media to improve their listening skills. As the result, the student’s perception of the use of podcasts in listening skills had an improvement in their effectiveness and uniqueness. The students believed that this media was interesting and informative in learning listening skills